Investigation on the physical and mechanical properties of waste newspaper deinked pulp by cellulase enzyme compared to conventional method - Iman Akbarpoor (Regional Information Center for Science and Technology (RICeST), 2011)
In this study, deinking of waste newspaper was investigated by conventional and enzymatic methods. Conventional deinking was done in pulping times of 10, 20 and 30 minutes along with different processes of washing, flotation and combined washing/   flotation. Enzymatic deinking was accomplished at different charges of 0.025, 0.05, 0.1 and 0.2% cellulase enzyme (based on oven-dried waste paper), pulping times of 10,15 and 20 minutes, pH range of 5-5.5 along with one-stage washing process. Optimum compositions were selected from chemical and enzymatic treatments and then physical and mechanical properties of the paper produced in optimum conditions were compared. Achieved results from comparison of the physical properties of optimum chemical and enzymatic treatments showed that, the paper produced from deinked pulp by conventional method had higher calliper, bulk and porosity. Using of 0.1% cellulase resulted the papers with higher tensile and breaking length compared to chemical treatments. The papers could be produced with similar burst and tear indexes compared to chemical treatments using of 0.1% cellulose, as well.